Spectral Doppler Measurements With 2-D Sparse Arrays - Mattesini, Paolo; Ramalli, Alessandro; Petrusca, Lorena; Basset, Olivier; Liebgott, Herve; Tortoli, Piero (IEEE transactions on ultrasonics, ferroelectrics, and frequency control, 2020)
The 2-D sparse arrays, in which a few hundreds of elements are distributed on the probe surface according to an optimization procedure, represent an alternative to full 2-D arrays, including thousands of elements usually organized in a grid. Sparse arrays have already been used in B-mode imaging tests, but their application to Doppler investigations has not been reported yet. Since the sparsity of the elements influences the acoustic field, a corresponding influence on the mean frequency (Fm), bandwidth (BW), and signal-to-noise ratio (SNR) of the Doppler spectra is expected. This article aims to assess, by simulations and experiments, to what extent the use of a sparse rather than a full gridded 2-D array has an impact on spectral Doppler measurements. Parabolic flows were investigated by a 3 MHz, 1024-element gridded array and by a sparse array; the latter was obtained by properly selecting a subgroup of 256 elements from the full array. Simulations show that the mean Doppler frequency does not change between the sparse and the full array while there are significant differences on the BW (average reduction of 17.2% for the sparse array, due to different apertures of the two probes) and on the signal power (Ps) (22 dB, due to the different number of active elements). These results are confirmed by flow phantom experiments, which also highlight that the most critical difference between sparse and full gridded array in Doppler measurements is in terms of SNR (-16.8 dB).